Characteristics of cellular composition of periodontal pockets - Hasiuk, Petro (Interv Med Appl Sci, 2016)
PURPOSE: The development of inflammatory periodontal disease in young people is an urgent problem of today's periodontology, and requires a development of new methods that would give an opportunity not only to diagnose but also for prognosis of periodontitis course in a given patients contingent. RESULTS: Cellular structure of periodontal pockets is presented by hematogenous and epithelial cells. Our results are confirmed by previous studies, and show that the penetration of periodontal pathogens leads to formation in periodontal tissue of a highly active complex compounds—cytokines that are able to modify the activity of neutrophils and reduce their specific antibacterial properties. Cytokines not only adversely affect the periodontal tissues, but also cause further activation of cells that synthesized them, and inhibit tissue repair and process of resynthesis of connective tissue by fibroblasts. CONCLUSION: Neutrophilic granulocytes present in each of the types of smear types, but their functional status and quantitative composition is different. The results of our cytological study confirmed the results of immunohistochemical studies, and show that in generalized periodontitis, an inflammatory cellular elements with disorganized epithelial cells and connective tissue of the gums and periodontium, and bacteria form specific types of infiltration in periodontal tissues.